A facile chemical cross-linking approach toward the fabrication of a sustainable porous ulvan scaffold. (July 2020) - Gajaria, Tejal K; Bhatt, Himadri; Khandelwal, Ankit; Vasu, Vihas T; Reddy, CRK; Shanthana Lakshmi, D
Ulvans represent one of the most abundant marine-derived macromolecular sulfated polysaccharides accounting for numerous biological applications including in one of the fastest growing field of biomedical sciences. Tissue engineering based on biologically inspired and naturally derived polymers has been one of the prime focuses of regenerative medicine. The present investigation is intended to explore an ionic cross-linking approach at higher pH lead by the calcium ions for casting cell growth promoting scaffolds out of the raw ulvan. The characterization studies using attenuated total reflectance infrared spectroscopy represent specific absorptions at 2950, 980, and 600 cm −1, whereas the x-ray diffraction showed a total absence of major crystalline peaks presenting significant shift to an amorphous state. The 1 H nuclear magnetic resonance study revealed functional group modifications in the backbone that might be potentially derived from calcium interactions with glucurorhamnose 3-sulfate and iduronorhamnose 3-sulfate. The atomic force microscopy together with field emission scanning electron microscopy and energy dispersive x-ray spectroscopy mapping revealed the resultant surface changes, whereas confocal microscopy z-stacking showed the cell proliferative activity as evident by the attainment of complete morphology. The combined chemical and biological response of the scaffold makes it a well suitable support for its cell culture and tissue engineering applications.